Defect in the industrialised building system (IBS) building / Mohd Esham Mamat ... [et al.] - Mamat, Mohd Esham; Mamter, Shahela; Bohari, Asmah Alia; Kipli, Kumalasari (2012)
The construction industry plays a major role in our country's economic growth. However, the industry is not without weaknesses. The challenges often occur in the area of productivity, efficiency, quality and the delivery of work. The intensive use of foreign unskilled workers, low technology equipment and out dated construction methods, have eventually caused low productivity and inefficiency of work at construction site. Industrialized Building System (IBS) is one of the improved building systems that is being introduced in the construction industry. The aim of this research is to determine the major type of building defects, causes and solution in the Industrialized Building System (IBS) building, although it carries many advantages. In many cases the multi storey buildings are not maintained properly, thus contributing further to poor image of Industrialized Building System (IBS) buildings. Given this situation, these buildings will require proper workmanship and materials to be used to rectify above problems. Therefore, this study will be carried out to investigate and identify the real defects which occurred and contaminated Industrialized Building System (IBS) system. The two case studies are to observe the real defect of this system. The interviews were also conducted by the researcher in order to identify the type and causes of defects that have occurred in Industrialized Building System (IBS) building. The findings researcher gets that the main problems of defect are caused by shoddy workmanship and poor supervision during construction show.